SEMANTIC AND STRUCTURAL FEATURES OF IRONIC EXPRESSIONS IN ENGLISH AND UZBEK - Abduqodirova Madina Abduqayum qizi (World Scientific Research Journal, 2025)
Annotation. This article analyzes the semantic and structural features of ironic expressions in English and Uzbek. It explores how irony functions within different cultural and linguistic contexts, examining both similarities and distinctions in structure, usage, and meaning. The study highlights how ironic expressions reflect national character, communication styles, and sociolinguistic norms, offering a comparative insight into the role of irony in both languages.